Kegiatan Bimbingan Belajar Untuk Meningkatkan Kemampuan Belajar Anak di Bimbingan Belajar Rumah Pintar Purwokerto - Wulan Tri Lestari; Raihan Nabil Tsabi; Fikri Haikal; Damar Gilang A (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
In the era of globalization and increasingly fierce competition, education plays a vital role in determining the future of children. This study aims to evaluate the effectiveness of tutoring activities in improving children's learning abilities at Rumah Pintar Purwokerto Tutoring. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that tutoring at Rumah Pintar, which offers personalized programs such as Baby Class, Toodler Activity, and Elementary and Junior High School Subjects, succeeded in improving children's understanding and learning skills. This tutoring applies a face-to-face learning model, with one teacher for one student, both at the tutoring center and at the student's home. Although there are obstacles such as scheduling between teachers and students, the findings show that the individualized approach and adequate facilities are able to overcome children's learning difficulties, increase motivation, and build their confidence. In conclusion, tutoring at Rumah Pintar Purwokerto is effective in improving children's learning abilities and providing additional support that is not always available in formal schools.